Teknik Mindfulness Dan Kecemasan Perempuan Sebagai Aparat Sipil Negara - Bayu Aji Santoso; Martaria Rizky Rinaldi (JIP (Jurnal Intervensi Psikologi), 2022)
The dual role of women who work as civil servants and become mothers can cause anxiety. Anxiety management is needed in order to be optimal in carrying out the role. This study aims to determine the effect of mindfulness techniques on anxiety in mothers who work as civil servants in Sumbawa Besar City. This research is a quasi-experimental quantitative research with a non-random pretest-posttest control group design. The sampling technique used nonrandom purposive, the subjects in this study were 13 people. Data collection in this study used the Hamilton Anxiety Rating Scale and the Kentucky Inventory of Mindfulness Skill as a check manipulation. Data analysis used Mann – Whitney U Test (Z=-2.164, p<0.050), and Wilcoxon Signed Ranks (Z=-2.384, p<0.050). This shows that mindfulness techniques are effective in reducing anxiety in mothers who work as civil servants.